Chronic Scapholunate Interosseous Ligament Disruption: A Systematic Review and Meta-Analysis of Surgical Treatments. (January 2020) - Daly, Lauren T.; Daly, Michael C.; Mohamadi, Amin; Chen, Neal
Background: Although many techniques have been described, there is no clear optimal surgical treatment for chronic scapholunate interosseous ligament (SLIL) disruption.Methods: We identified 255 articles reporting outcomes of SLIL reconstruction. Of these, 40 studies (978 wrists) met eligibility requirements and reported sufficient data on radiographic outcomes to be included in the study. The mean and standard deviation of preoperative and follow-up assessments including scapholunate gap (SLG) and scapholunate angle (SLA) were used to calculate pooled standardized mean differences (SMD) with 95% confidence intervals (CIs). For other radiographic or clinical outcomes, there were not enough reported data to calculate a pooled effect size, and pooled nonstandardized comparisons were made.Results: The SMD between preoperative and postoperative SLA in tenodesis reconstruction was 0.7 (CI, 0.29 to 1.11, P = .001) and 0.04 (CI, –0.27 to 0.38, P = .8) for capsulodesis reconstruction. For SLG, tenodesis demonstrated an SMD of 1.1 (CI, 0.6 to 1.55, P < .001) compared with 0.1 (CI, –0.36 to 0.59, P = .6) for capsulodesis reconstruction. Tenodesis had a significant improvement compared with capsulodesis in SLA ( P = .01) and SLG ( P = .005). Tenodesis also showed improvement in grip strength and Disabilities of the Arm, Shoulder and Hand scores.Conclusions: Comparing preoperative and postoperative radiographic measurements, tenodesis reconstruction demonstrated significantly improved SLG and SLA relative to capsulodesis. Interpreted in the context of the limitations, existing data demonstrates some benefit of tenodesis reconstruction.